Deep Brain Stimulation for Refractory Temporal Lobe Epilepsy. Current Status and Future Trends - Velasco, Francisco; Saucedo-Alvarado, Pablo E.; Vazquez-Barron, Daruny; Trejo, David; Velasco, Ana Luisa (Frontiers in Neurology, 2022)
A comparative analysis of the targets for deep brain stimulation (DBS) to treat refractory temporal lobe epilepsy and the rationale for its use is presented, with an emphasis on the latency to obtain the significant antiepileptic effect and the long-term seizure control. The analysis includes consideration of surgical techniques currently used to optimize antiseizure effects and decrease surgical risks. Seizure control is similar for programed DBS and DBS responsive to abnormal cortical or subcortical electroencephalogram (EEG) activity. There is no difference in the long-term seizure control between programmed and responsive and intermittent or continuous DBS. However, intermittent programed DBS may have a significant antiseizure effect starting in the first month when applied to a non-sclerotic tissue such as the parahippocampal cortex. DBS induces no neuropsychological deterioration.